2004
DOI: 10.1046/j.1365-2648.2003.02862.x
|View full text |Cite
|
Sign up to set email alerts
|

The description and evaluation of a longitudinal pilot study of a smoking relapse/reduction intervention for perinatal women

Abstract: Future research is needed to evaluate the effectiveness of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
(29 reference statements)
0
13
0
2
Order By: Relevance
“…As such, MAPS/MAPS+ is responsive to research indicating that motivation for quitting and maintaining abstinence varies over short periods of time (Hughes et al, 2005;Werner et al, 2004) and differs from other interventions that conceptualize motivation as stage based and less volatile (e.g., Hajek et al, 2001;Morasco, Dornelas, Fischer, Oncken, & Lando, 2006;Valanis et al, 2001). Similar to other emerging interventions (Bullock et al, 2009;Chalmers et al, 2004;Gaffney, 2006), MAPS/MAPS+ is a holistic approach in which numerous issues of relevance to pregnant and postpartum women are addressed. Results suggest that an intervention that treats women's smoking within a larger framework of wellness, and that recognizes and adapts to moment-to-moment changes in motivation, is more efficacious than UC for relapse prevention among women who spontaneously quit smoking during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…As such, MAPS/MAPS+ is responsive to research indicating that motivation for quitting and maintaining abstinence varies over short periods of time (Hughes et al, 2005;Werner et al, 2004) and differs from other interventions that conceptualize motivation as stage based and less volatile (e.g., Hajek et al, 2001;Morasco, Dornelas, Fischer, Oncken, & Lando, 2006;Valanis et al, 2001). Similar to other emerging interventions (Bullock et al, 2009;Chalmers et al, 2004;Gaffney, 2006), MAPS/MAPS+ is a holistic approach in which numerous issues of relevance to pregnant and postpartum women are addressed. Results suggest that an intervention that treats women's smoking within a larger framework of wellness, and that recognizes and adapts to moment-to-moment changes in motivation, is more efficacious than UC for relapse prevention among women who spontaneously quit smoking during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an attempt to tailor a smoking-cessation program to pregnant smokers, Chalmers et al involved pregnant smokers in program improvement by asking for suggested changes in the current pilot program. However, only a few women offered suggestions for changes (Chalmers et al, 2004). In other research designed to evaluate interventions of varying intensity tailored for pregnant smokers, no difference in the abstinence rate (7-day point prevalence) was detected at 12 months (McBride et al).…”
mentioning
confidence: 98%
“…Development of tailored smoking-cessation interventions have been previously suggested for special populations (Fiore et al, 2004). Components of tailored smoking cessation interventions differ greatly with mixed results (Chalmers et al, 2004;Hollis et al, 2005;Lancaster and Stead, 2005;Lancaster, Stead, Silagy, and Sowden, 2000;McBride et al, 1999;O'Connell et al, 2003O'Connell et al, , 2004Strecher et al, 2005;Swartz, Noell, Schroeder, and Ary, 2006;Wright, Weinman, and Marteau, 2003). Given that current programs do not always meet the needs of women smokers, there is a critical need to develop more effective smoking cessation programs for women (Piper et al, 2001;Sarna and Bialous, 2004;Schmitz, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no safe amount of smoking during pregnancy. Consequently perinatal health care providers, including nurses, must actively support women's efforts to stop smoking [7,9,10].…”
Section: Introductionmentioning
confidence: 99%